1994
DOI: 10.1083/jcb.126.5.1299
|View full text |Cite
|
Sign up to set email alerts
|

Altered localization and cytoplasmic domain-binding properties of tyrosine-phosphorylated beta 1 integrin.

Abstract: Abstract. We describe a novel approach to study tyrosine-phosphorylated (PY) integrins in cells transformed by virally encoded tyrosine kinases. We have synthesized a peptide (PY/~ peptide) that represents a portion of the cytoplasmic domain of the/~1 integrin subunit and is phosphorylated on the tyrosine residue known to be the target of oncogenic tyrosine kinases. Antibodies prepared against the PY/3~ peptide, after removal of cross-reacting antibodies by absorption and affinity purification, recognized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…14, nontransformed ␤1A-GD25, Y783͞795F, Y783F, and Y795F cells all have a well-developed F-actin-containing cables that terminate in ␤1A-and vinculin-containing focal contacts. In v-src-transformed GD25 cells expressing wild-type or Y795F mutant ␤1A, ␤1A was present in circular podosomes, as reported previously for a variety of src-transformed cells (4,11,22,23) (Fig. 4A).…”
Section: Cells Including Y783͞795f Cells Assembled Fitc-fibronectinsupporting
confidence: 51%
See 1 more Smart Citation
“…14, nontransformed ␤1A-GD25, Y783͞795F, Y783F, and Y795F cells all have a well-developed F-actin-containing cables that terminate in ␤1A-and vinculin-containing focal contacts. In v-src-transformed GD25 cells expressing wild-type or Y795F mutant ␤1A, ␤1A was present in circular podosomes, as reported previously for a variety of src-transformed cells (4,11,22,23) (Fig. 4A).…”
Section: Cells Including Y783͞795f Cells Assembled Fitc-fibronectinsupporting
confidence: 51%
“…v-src-transformed fibroblasts exhibit several properties related to cell adhesion, including morphological changes, increased growth rate, loss of anchorage dependence of growth, loss of focal contacts, and decreased synthesis and deposition of extracellular matrix (3)(4)(5)(6)(7). v-src causes extensive protein tyrosine phosphorylation of cellular proteins (3,8), including tyrosines in the NPXY motifs of the cytoplasmic domain of the ␤1A integrin subunit (9)(10)(11). The role of phosphorylation of ␤1 integrins in transformation by v-src is not known.…”
Section: R Ous Sarcoma Virus (Rsv) Is the First Known Tumor Virusmentioning
confidence: 99%
“…Although increased ␤ 1 -integrin tyrosine phosphorylation has been observed in v-Src-transformed cells (24) and increased serine phosphorylation in parietal endoderm has been demonstrated following treatment with okadaic acid (39), the transient nature of ␤ 1 -integrin phosphorylation has limited most site-specific functional studies to using mutational analysis of conserved cytoplasmic serine-threonine residues without direct evidence of conditional phosphorylation. Increased pressure stimulates robust phosphorylation of ␤ 1 -integrin S785 and T788/9 residues and provides a unique model by which to study the role of site-specific phosphorylation events on ␤ 1 -integrin conformational activation and cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of NPxY tyrosine phosphorylation have been studied extensively, conflicting reports demonstrate differential effects on integrin function (reviewed in Legate and Fassler, 2009). Several lines of evidence indicate that these mutations activate vertebrate integrins by enhancing binding of the adapter protein, talin (Johansson et al, 1994;Datta et al, 2002;MillonFrémillon et al, 2008;Oxley et al, 2008;Anthis et al, 2009b), which has an established role in activating integrins (reviewed in Calderwood, 2004). We tested the effects of the YY>FF mutation in flies using fluorescence recovery after photobleaching (FRAP) and found that the mobile fraction, a proven method for measuring integrin turnover (Yuan et al, 2010), was lower than WT at MTJs (Supp.…”
Section: Mutational Analysis Of Drosophila B-integrinmentioning
confidence: 99%